Yagi-Uda Antenna for Navigational Aids Using HFSS - Ramesh P.; V. Mathivanan (Institute of Advanced Engineering and Science, 2017)
In this paper, the ultra high frequency of yagi-uda antenna for navigational has been designed to improve the usable bandwidth by improving the stability of the radiation patterns. The frequency band of ultra high frequency is 300-3000 MHZ. The main aim of this paper is to reduce the loss, improve the gain and also to enhance the efficiency of ultra high frequency yagi-uda antenna for utilizing the navigational aids. The proposed UHF band of Yagi-Uda antenna has been designed by using ANSYS HFSS tool for the application of navigational aids. The characteristics specifications of yagi-uda antenna such as Radiation pattern, S11 (return loss), impedance matching and gain are analyzed in this work.